Review Paper on Application of Data Mining on Healthinformatics - Chaflekar, Snehal H; Shinganjude, R (International Journal of Computer Sciences and Engineering, 2018)
Data mining is a relatively new field of research whose major objective is to acquire knowledge from large amounts of data. In medical and health care areas, due to regulations and due to the availability of computers, a large amount of data is becoming available. On the one hand, practitioners are expected to use all this data in their work but, at the same time, such a large amount of data cannot be processed by humans in a short time to make diagnosis, prognosis and treatment schedules. Data mining in the medical domain works on the past experiences (data collected) and analyse them to identify the general trends and probable solutions to the present situations. This paper is concerned with the application of data mining techniques in the domain of the medical field of heart diseases/attack. We carried out extensive experiments applying different data mining techniques including Relevance analysis, Association Rules Mining and Clustering. We report the findings which are very promising.